APPLICATION OF E-GOVERMENT SYSTEM AS AN EFFORT TO CREATE A CONDUCIVE INVESTMENT CLIMATE IN BANYUWANGI REGENCY - Arief Maulana; Hafiza Aryaputri; Fandi Rizki Rosyari (NATAPRAJA, 2020)
One of the efforts made by the government to increase development is by developing the field of investment, because economically investment is the first step in production activities. In this regard, to create a realization of sustainable investment, a conducive investment climate is needed. A conducive investment climate in the economy is a hope for the community, investors, business people and the government. This study aims to analyze and explain the strategies of the Banyuwangi Regency Government as an effort to create a Conducive Investment Climate that is useful for regional development. This research was conducted using qualitative methods with a case study approach. Data collection techniques that will be used in this study include interviews, focus group discussions, documentation and literature studies. The results showed that BanyuwangiRegency implemented regulations on investment by implementing several e-Government applications that had the function of transparency, accountability, and facilitating public services related to investment. E-government leads to good governance because government services are more transparent, effective and efficient so as to form public trust which has an impact on increasing investment interest by investors. The increase in investment was also caused by policies or regulations that favored the creation of a conducive investment climate.